2000
DOI: 10.1104/pp.124.4.1800
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Characterization in Yeast of a Gene for ArabidopsisS-Adenosylmethionine:Phospho-EthanolamineN-Methyltransferase

Abstract: Saccharomyces cerevisiae opi3 mutant strains do not have the phospholipid N-methyltransferase that catalyzes the two terminal methylations in the phosphatidylcholine (PC) biosynthetic pathway. This results in a build up of the intermediate phosphatidylmonomethylethanolamine, causing a temperature-sensitive growth phenotype. An Arabidopsis cDNA library was used to isolate three overlapping plasmids that complemented the temperature-sensitive phenotype. Phospholipid analysis showed that the presence of the clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
104
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 58 publications
8
104
0
Order By: Relevance
“…motifs (8,13,14). Isothermal titration calorimetry (ITC) was used to evaluate the stoichiometry and energetics of ligand binding to AtPMT2.…”
Section: Substratementioning
confidence: 99%
See 1 more Smart Citation
“…motifs (8,13,14). Isothermal titration calorimetry (ITC) was used to evaluate the stoichiometry and energetics of ligand binding to AtPMT2.…”
Section: Substratementioning
confidence: 99%
“…by functional complementation of a yeast mutant (13). Subsequent work demonstrated that silencing of atpmt1 resulted in temperature-sensitive male sterility and salt hypersensitivity and that the Arabidopsis xipotl1 mutant, which disrupts atpmt1, is characterized by a short primary root, increased lateral root formation, and short epidermal cells (24,25).…”
mentioning
confidence: 99%
“…These pathways allow for the use of exogenous choline and other phospholipids to be used for the synthesis of the major membrane phospholipid. In contrast, plants endogenously synthesize phosphocholine (pCho) 2 via the sequential methylation of phosphoethanolamine (pEA) in the phosphobase methylation pathway (3)(4)(5)(6)(7)(8). Interestingly, the plant-like phosphobase methylation pathway is also found in the free-living nematode Caenorhabditis elegans and the protozoan parasite Plasmodium falciparum, which causes malaria (9 -14).…”
mentioning
confidence: 99%
“…1A) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although the PMT found in plants, nematodes, and protozoans all catalyze the S-adenosylmethionine (AdoMet)-dependent methylation of pEA to pCho, the physical organization of the methyltransferase domains in these enzymes from plants (type 1), protozoa (type 2), and nematodes (type 3) differs dramatically (Fig.…”
mentioning
confidence: 99%
“…Consistent with higher phospholipid levels, HpNMT2 transcripts encoding a putative phosphocholine-producing enzyme involved in de novo phospholipid biosynthesis (Bolognese and McGraw, 2000;Jost et al, 2009;BeGora et al, 2010) were more abundant in young than in mature leaves of P-limited H. prostrata. Interestingly, higher Po concentrations and NMT transcript abundance in young leaf tissues are also striking features of a highly P-efficient wheat (Triticum aestivum) cultivar (Aziz et al, 2014).…”
Section: Young H Prostrata Leaves Show Delayed Development Of Functimentioning
confidence: 75%